Integrated serum pharmacochemistry and network pharmacology to reveal the kernel material basis and underlying mechanisms of the fuzi-lizhong pill for ulcerative colitis - You Huang; Xia Lin; Qiuhong Wu; XunJian Wu; Shasha Yang; Yidian Dong; Chaomei Fu; Wei Lin; Zhen Zhang (Journal of Traditional and Complementary Medicine)
Background: In traditional Chinese medicine, Fuzi-Lizhong pill (FLZP) has been used for millennia as a treatment for the Spleen-Kidney-Yang-deficiency (SKYD) diseases. FLZP has increasingly been employed in the clinic as a therapeutic option for ulcerative colitis with SKYD syndrome (SKYD-UC). In the present study, we revealed the kernel material basis and underlying mechanisms of the FLZP for treating SKYD-UC. Methods and results: The therapeutic effects of FLZP were assessed in SKYD-UC rats. In total, 55 absorbed components of FLZP were identified, thus forming the main material basis for the use of FLZP for treating SKYD-UC. Network pharmacology analyses revealed that the ability of FLZP to exert multi-target synergistic activity was found to be related to both antioxidant and anti-inflammatory activity. More specifically, FLZP was suggested to alleviate SKYD-UC through the regulation of targets associated with inflammation such as interleukin-6 (IL-6), myeloperoxidase (MPO), and tumor necrosis factor-α (TNF-α), while also regulating the mitogen-activated protein kinase (MAPK), TNF, and phosphoinositol-3 kinase-RAC-alpha serine/threonine-protein kinase (PI3K-Akt) pathways. Ultimately, the integration of network analyses, molecular docking studies, and Pearson correlation analyses enabled the identification of 9 core compounds (including linolenic acid, liquirtigenin, 7-hydroxycoumarin, glycyrrhizic acid, 6-shogaol, dehydro-10-gingerdione, caffeic acid, 6-gingerol, liquiritin), which can serve as kernel material basis for FLZP in the treatment of SKYD-UC. Conclusion: Together, these findings offer a valuable foundation for additional research focused on the mechanistic effects and broader clinical application of FLZP as a treatment option for SKYD-UC.